Supposed concept: rotation – the method of the universe existence - Velgas L. B., Iavolinskaia L. L. (Interactive science, 2018)
in this concept, authors seek to prove that all planets revolve around their axes because of the impact of their satellites. The rotation of the joint gravitational force is similar for all planets and for the Sun. The Sun and each planet can have several satellites. The joint gravitational force of each pair – the satellite of the planet and the planet itself, the satellite of the Sun and the Sun itself, if the joint force of gravity, moves due to the motion of the satellite in orbit, rotates the planet or the Sun. The article proves that the joint gravity of the Moon and the Earth, which moves around the Earth due to the Moon's rotation around the Earth, rotates the Earth around its axis. And that the joint gravity of the Moon and Earth holds the Moon so that the side of the Moon with a larger mass is located in the direction of Earth. All satellites (there are more than 150 of them) are in the same rigid stable position – depending on their planets. And all the satellite planets in the solar system in rotation around their axes depend on their satellites. The Earth and the Moon in this matter are not original. Researchers provide evidence of the absence of a thermonuclear reaction on stars and the fact that the energy of solar radiation is electrical energy, not thermonuclear. In addition, the existence of dark matter is questioned in the work. The authors also prove that it is necessary to exclude the term "synchronization", which has no right to exist due to the absence of satellites rotation of the planets around their axes.
Keywords: Солнечная система; Solar system; магнетизм; электромагнетизм; орбитальное перемещение; планета-спутник; астероид; magnetism; electromagnetism; orbital movement; satellite planet; asteroid; тёмная материя; dark matter